Validation of Psoriasis Diagnoses in the Danish National Patient Register - Nikolai Dyrberg Loft; Christian Harbo Andersen; Anne-Sofie H; Jacob P. Thyssen; Lone Skov; Alexander Egeberg (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)